2010
DOI: 10.1177/1049732310374062
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Connections Between the Subjective Experience of Health and Quality of Life in Old Age

Abstract: The importance of qualitative methods in quality of life (QoL) studies is being increasingly recognized. Whereas attention has mainly focused on the exploration of relevant domains, subjective well-being, and representations of health in aging, less consideration has been given to relations among different QoL domains. We aimed in this research to identify connections between subjective health and other relevant domains from the perspective of older adults. We identified four central categories: adaptation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
2
21
0
1
Order By: Relevance
“…Bowling (1995) found that the relationships with family and health were the main dimensions of QoL from the individuals' perspective. In the same way, health and family, particularly in relation to partners, children and grandchildren were the central QoL aspects based on grounded theory research (Prieto-Flores et al 2010). Another key dimension reported by the participants was financial status.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Bowling (1995) found that the relationships with family and health were the main dimensions of QoL from the individuals' perspective. In the same way, health and family, particularly in relation to partners, children and grandchildren were the central QoL aspects based on grounded theory research (Prieto-Flores et al 2010). Another key dimension reported by the participants was financial status.…”
Section: Discussionmentioning
confidence: 95%
“…However, its contribution to QoL is variable with discrepancies between health status and QoL: many older adults report a satisfactory QoL despite having several health problems, a finding that may be due to other factors that help to compensate health decline (Fernandez-Mayoralas and Rojo Pérez 2005;Grimby and Svanborg 1997;Grimby and Wiklund 1994;Prieto-Flores et al 2010). In addition, the process of adaptation to health deterioration in old age contributes to the reduction of the relative importance of health in QoL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, there was evidence of the importance of physical functioning (Azpiazu et al 2002;Bowling et al 1993;Smith et al 2002), neighborhood (Bowling et al 2002), satisfaction with health (Michalos et al 2003), age (Smith et al 2002), finances (Michalos et al 2003;Smith et al 2002), social activities (Smith et al 2002), spare time (Guallar-Castillón et al 2005), and family (Farquhar 1995;Prieto-Flores et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Pomembna ugotovitev poglobljenega kvalitativnega dela raziskave je, da se tveganja med seboj izrazito povezujejo in da za posameznika postanejo neobvladljiv problem, ko se začnejo prekrivati in medsebojno krepiti. Podobno kot ugotavljajo drugi avtorji, tudi iz naših analiz sledi, da so temeljna in za starejše najbolj pereča tista tveganja, ki ogrožajo njihovo avtonomnost in vodijo v odvisnost (24)(25)(26)(27). Pomen neodvisnosti in samostojnosti je v literaturi pogosto omenjen in v splošnem prepoznan kot pomemben.…”
Section: Razpravaunclassified